Corynebacterium species nasal carriage in pigs and their farmers in Bavaria, Germany: implications for public health. (13th September 2014) - Boschert, V.; Berger, A.; Konrad, R.; Huber, I.; Hörmansdorfer, S.; Zöls, S.; Eddicks, M.; Ritzmann, M.; Sing, A.
Abstract : Reports on cases of human diphtheria caused by toxigenic Corynebacterium ulcerans that were linked to occupational swine contact as well as isolation of C ulcerans from wild boars have suggested that pigs might serve as reservoir for human infections. Therefore, a prevalence study on Corynebacterium species nasal carriage in pigs and their farmers was performed between August 1 and December 31, 2009, in 41 swine farms from Bavaria, Germany. All 411 asymptomatic pigs and 29 of 30 healthy farmers were colonised with Corynebacterium strains of up to 11 different species. No potentially toxigenic Corynebacterium strain was isolated either from the pigs or from their farmers, respectively. The patterns of the species composition in the pigs and the farmers were very similar, suggesting a potential transmission of strains between animals and humans.